NEW CONCEPT AND CURRENT UNDERSTANDING OF INTEGRATED FORENSIC INVESTIGATION - L. Edzhubov; A. Usov; O. Miklyaeva (Теория и практика судебной экспертизы, 2014)
The paper carries on the discussion of theoretical and procedural aspects of integratedforensic investigation: the capacity of a forensic examiner to evaluate a conclusion madeby a specialist in a different forensic discipline, the legal status of integrated forensicinvestigation, differences between the terms 'specialization' and 'specialism', classificationof forensic investigations into 'commissioned' and 'integrated', etc.